Peningkatan Kapasitas Entrepreneurship Melalui Pelatihan dan Magang Bagi Tenant di Universitas Muhammadiyah Sidoarjo - Wiwik Sulistiyowati; Ida Agustini; Hadiah Fitriyah (Universitas Mathla'ul Anwar Banten, 2016)
Universitas Muhammadiyah Sidoarjo is one university located in Sidoarjo from year to year working to improve its quality. During this time centered on the entrepreneurial activities of SMEs entrepreneurial student affairs, but in an increase in the capacity to be entrepreneurial is not optimal. The purpose of science and technology program for Entrepreneurship (IBK) at the University of Muhammadiyah Sidoarjo (UMSIDA), namely the establishment of new independent entrepreneurs tenacious, resilient, creative and able to provide innovation into market demand. With the IBK this program, students are expected to be part of society that can create jobs, reduces unemployment and become change agents of social life that is more powerful and useful. Method approach entrepreneurship capacity building program is using PALS (Participatory Action Learning System). So that the target output of this activity is the training to increase the capacity of tenants (students) in biddng kewirauahaan and to improve the quality of products for business tenants.